Atrial Cardiopathy and Cryptogenic Stroke - Kato, Yuji; Takahashi, Shinichi (Frontiers in Neurology, 2022)
Recent advances in pathophysiology suggest that a pathological atrial substrate can cause embolic stroke even in patients without atrial fibrillation (AF). This pathological condition is called “atrial cardiopathy”, which indicates atrial structural and functional disorders that can precede AF. The objective of this narrative review was to provide a current overview of atrial cardiopathy and cryptogenic stroke. We searched the PubMed database and summarized the recent findings of the identified studies, including the pathogenesis of atrial cardiopathy, biomarkers of atrial cardiopathy, relationship between atrial cardiopathy and cryptogenic stroke, and therapeutic interventions for atrial cardiopathy. Abnormal atrial substrate (atrial cardiopathy) that leads to AF can result in embolic stroke before developing AF, and may explain the source of cryptogenic stroke in some patients. Although there are several potential biomarkers indicative of atrial cardiopathy, P-wave terminal force in lead V1 (>5,000 μV* ms), N-terminal pro-brain natriuretic peptide (>250 pg/ml), and left atrial enlargement are currently promising biomarkers for the diagnosis of atrial cardiopathy. Because the optimal combination and thresholds of biomarkers for diagnosing atrial cardiopathy remain uncertain, atrial cardiopathy represents a spectrum disorder. The concept of atrial cardiopathy appears to be most valuable as a starting point for therapeutic intervention to prevent stroke. Validation of the diagnosis of atrial cardiopathy and whether it can be used as a new therapeutic target for direct oral anticoagulants are currently being covered in the ARCADIA trial.